Course of mental symptoms in patients with stress-related exhaustion: does sex or age make a difference? - Glise, Kristina (BioMed Central, 2012)
BACKGROUND: Long-term sick leave due to mental health problems, especially among women, is a substantial problem in many countries, and a major reason for this is thought to be psychosocial stress. The recovery period of different patient groups with stress-related mental health problems can differ considerably. We have studied the course of mental health symptoms during 18 months of multimodal treatment in relation to sex and age in a group of patients with stress-related exhaustion. METHODS: The study group includes 232 patients (68% women) referred to a stress clinic and who fulfilled the criteria for Exhaustion Disorder (ED). The majority also fulfilled diagnostic criteria for depression and/or anxiety; this was similar among women and men. Symptoms were assessed at baseline, three, six, 12 and 18 months by the Shirom-Melamed Burnout Questionnaire (SMBQ) and the Hospital Anxiety and Depression scale (HAD). A total SMBQ mean score of ≥ 4 was used to indicate clinical burnout, which correlates well with the clinical diagnosis of ED. RESULTS: There were no statistically significant differences between women and men or between young and old patients in the self-reported symptoms at baseline. The proportion that had high burnout scores decreased over time, but one-third still had symptoms of clinical burnout after 18 months. Symptoms indicating probable depression or anxiety (present in 34% and 65% of the patients at baseline, respectively) declined more rapidly, in most cases within the first three months, and were present only in one out of 10 after 18 months. The course of illness was not related to sex or age. The duration of symptoms before seeking health care, but not the level of education or co-morbid depression, was a predictor of recovery from symptoms of burnout after 18 months. CONCLUSIONS: The course of mental illness in patients seeking specialist care for stress-related exhaustion was not related to sex or age. The burden of mental symptoms is high and similar for men and women, and at the 18 month follow-up, one-third of the study group still showed symptoms of burnout. A long duration of symptoms before consultation was associated with a prolonged time of recovery, which underlines the importance of early detection of stress-related symptoms.